P032 Capture of IGA immune complexes and enrichment in IGA IG gene expression suggest a role for synovial FCRL4+ B cells in the link between mucosal and joint inflammation. (21st February 2018) - Cameron, J; Clay, E; Amara, K; Vidal Pedrola, G; Sippl, N; Filer, A; Raza, K; Malmstrom, V; Scheel-Toellner, D
Abstract : Introduction: Increasing evidence points to the autoimmune process of rheumatoid arthritis (RA) originating at mucosal surfaces. Previous work from our group described a subset of B cells in the synovium and synovial fluid (SF) of RA patients distinguishable by their expression of Fc-like receptor 4 (FcRL4) and elevated expression of RANKL, indicating a unique pathogenic function. 1, 2 B cells expressing FcRL4 were originally described as a distinct memory B cell subset in human tonsils where they are localised in the epithelium. 3 We have recently shown in RA that they are enriched in clones recognising citrullinated autoantigens. 3 Recent in vitro work suggested that FcRL4 is a low affinity receptor for aggregated IgA. 4 Objectives: Investigate the interactions between IgA and FcRL4 and FcRL4+ B cells using tonsil and SF B cells, and transfected cell lines. Examine the distribution of Ig classes by flow cytometry and PCR. Methods: Mononuclear cells were isolated from SF (n=10) and tonsil, labelled for CD19, FcRL4, IgA, and IgG and analysed by flow cytometry. In experiments identifying BCRs and relative loads of surface bound IgA; SFMCs were washed in an acidic buffer to remove receptor-bound proteins before staining. Heat-aggregated purified human IgA was added to assess IgA binding to FcRL4 +B cells. Single B cells were sorted from SF of RA patients and their constant region genes probed for identification of their Ig subclass by PCR. Results: We show that ex vivo SF FcRL4 + B cells have a significantly higher load of IgA bound to their surface (p=0.0001) than FcRL4 - B cells. Following in vitro removal of surface bound IgA, FcRL4 +B cells bind heat-aggregated IgA (p=0.03 vs control). We also demonstrate that a significantly higher proportion of FcRL4 + B cells use IgA BCRs (p=0.0061) by flow cytometry, and by probing constant region genes by PCR an enrichment for Ig genes for coding the IgA1 isotype (p=0.009) was found. Furthermore, three out of eight of the antibodies recognising citrullinated peptides had been cloned from FcRL4 + IgA + B cells. Conclusions: In conclusion, their specificity for citrullinated antigens, ability to capture IgA immune complexes through via FcRL4 and enrichment in IgA1 subclass expression, suggest a role for FcRL4 +B cells in the mucosal origin of joint inflammation. References: . Yeo L, et al. Ann Rheum Dis2011;70:2022–2028. doi:10.1136/ard.2011.153312 . Yeo L, et al. Ann Rheum Dis2015;74:928–935. doi:10.1136/annrheumdis-2013-204116 . Amara K, et al. J. Autoimmun2017. doi:10.1016/j.jaut.2017.03.004 . Wilson TJ, et al. J Immunol2012;188;4741–4745. doi:10.4049/jimmunol.1102651 Acknowledgements: This work was supported by the Medical Research Council UK, Rheumatoid Arthritis Pathogenesis Centre of Excellence, and Karolinska Institutet Foundations for Rheumatology Research. Disclosure of interest: None declared